Biosynthesis and characterization of chitosan nanoparticles, determination of its antifungal and antiaflatoxigenic against Aspergillus flavus isolates - Samira Taha Bapir; Zainab Mohammed Al Zubaidy (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Aflatoxin is a mycotoxin generated mostly by the fungus Aspergillus flavus, which may be found in food and feed. It is a carcinogenic poison for both humans and animals. The goal of this investigation was to see if toxicogenic A. flavus strains might be found on nuts in the Kurdistan Region. A total of Fifty nut samples. The colony color of A. flavus and texture were used to identify macromorphological qualities, whereas the spore color, size, structure, conidiophore structure, and vesicle shape were used to assess micromorphological properties. Direct imaging of the UV fluorescence of A. flavus colonies on coconut agar media (CAM) was used to detect aflatoxin formation. Natural compounds, such as chitosan, have been suggested as a way to prevent fungal infection because of their extensive and well-known antibacterial action against a variety of microorganisms. The goal of this entry was to morphologically characterize and determine aflatoxigenic A. flavus isolates, characterize nanoparticles using UV–visible, X-ray diffraction (XRD), Energy-dispersive X-ray (EDX), and scanning electron microscope (SEM) analyses, and determine the formulations' in vitro antifungal activity on the treated fungus. Individual concentrations were created by altering the percentages of ingredients such chitosan solution, chitosan nanoparticles, glycerol, and canola oil. The final concentrations of chitosan solution and chitosan nanoparticles were 20% and 2% respectively. Chitosan nanoparticles completely inhibit the growth of A. flavus at 2%.